Migration as part of the state's foreign policy: Case study Slovakia - Martina Bolečeková; Barbora Olejárová (CES Working Papers, 2017)
Border protection and the right to decide about entry and residence of foreign nationals on the state's territory are regarded as the most important manifestations of the state's sovereignty and usually fall under the control of the police forces and ministries of interior of individual states. Yet, in some cases, the migration flows heading to or by-passing the state's territory can transform from the issue of domestic policy to the foreign policy realm. The paper will outline conditions which have to be met for such transformation, as well as the consequences of this process on the example of a particular state – the Slovak Republic.
Keywords: 330; domestic policy; foreign policy; migration; security; Slovak Republic